INTERPRETASI PENERAPAN BIRRUL WALIDAIN BAGI SANTRI DI LINGKUNGAN PESANTREN (Studi Fenomenologi di Yayasan Rumah Santri Al – Ridwan Karawang) - Halizah, Siti Nur; Taufik Mustofa; Nia Karnia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Birrul Walidain is the obligation of children to show devotion and respect to their parents. However, its implementation among Islamic boarding school students (santri) faces limitations due to physical distance, communication restrictions, and demanding daily activities. This study aims to understand the interpretation of Birrul Walidain, the experiences of santri in practicing devotion to their parents, and the meanings they attribute to the obstacles they encounter. This research employed a qualitative approach using Alfred Schutz's phenomenological method at the Al-Ridwan Santri House Foundation in Karawang. Data were collected through interviews, observations, and documentation, and subsequently analyzed. The findings reveal that santri interpret Birrul Walidain as respect, obedience, prayer, and efforts to make their parents happy. Despite limited direct interaction, santri continue to practice Birrul Walidain through prayers, diligence in learning, maintaining good character, and adhering to the boarding school's regulations. Furthermore, conditions such as being orphaned, underprivileged, or coming from broken-home families are not perceived as barriers; instead, they serve as motivation to appreciate their parents' struggles more deeply and enhance their devotion to them. These findings indicate that Birrul Walidain is not only manifested through physical presence but also through religious awareness and everyday life practices.